2010
DOI: 10.1111/j.1526-100x.2010.00655.x
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Old Forest Features in Coast Redwood Forests Using Early‐stage Variable‐density Thinning

Abstract: To accelerate development of old forest features in coast redwood, two thinning treatments and an unthinned control were compared in three treatment areas in north coastal California. One thinning treatment was designed to restore old forest densities of 125 trees/ha and the other 250 trees/ha representing a one-step and partial treatments to the desired stand density. Four years after treatment, numbers of trees had increased in the thinning treatments due to recruitment of new trees, but had decreased in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 16 publications
4
52
1
Order By: Relevance
“…A similar result was reported by O'Hara et al [45], who found that average volume for residual trees was 124% and 107% greater after 4 years in the low-and moderate-density treatment, respectively, but only 72% larger in the control treatment. This was because thinning conducted in the transformation treatments released competition, which resulted in an increase in resource availability for residual trees.…”
Section: Growth Pattern and Determination Of Optimal Transformation Tsupporting
confidence: 76%
“…A similar result was reported by O'Hara et al [45], who found that average volume for residual trees was 124% and 107% greater after 4 years in the low-and moderate-density treatment, respectively, but only 72% larger in the control treatment. This was because thinning conducted in the transformation treatments released competition, which resulted in an increase in resource availability for residual trees.…”
Section: Growth Pattern and Determination Of Optimal Transformation Tsupporting
confidence: 76%
“…Thinning and partial harvests can restore earlyseral habitat and associated diversity within mature second-growth stands, whereas traditional forest management aimed at maximizing production tends to constrain these community or ecosystem properties (Ares et al 2009, Swanson et al 2011, Donato et al 2012. Thinning can also accelerate development of oldgrowth characteristics within younger second-growth stands (Bauhus et al 2009, O'Hara et al 2010, Dodson et al 2012. However, reductions in on-site C storage and late-seral species richness are also associated with thinning.…”
Section: Discussionmentioning
confidence: 99%
“…Thinning is a common management activity that provides income for landowners and material for the wood manufacturing industry, while increasing vigor and growth rates of residual trees (Nyland 2002). Over the past two decades, forest scientists have made progress toward understanding how common management practices such as thinning can be applied to increase plant diversity and accelerate the development of late-successional habitat features (Thomas et al 1999, Ares et al 2009, Bauhus et al 2009, O'Hara et al 2010, Dodson et al 2012. The focus on late-seral conditions resulted from large reductions in extent of old growth in temperate forests and concern for associated species (FEMAT 1993, Lorimer and White 2003, Nonaka and Spies 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Forest restoration, or the silvicultural manipulation of second-growth stands to expedite the acquisition of old-growth forest characteristics, has emerged as a top priority for managers of forest reserves in northern coastal California [1][2][3][4]. Upland second-growth stands that emerged after the clearcutting of old-growth redwood forests are often characterized by conditions that foretell stagnation: very high tree densities, presence of non-native tree species, and suppressed stand growth and development [5][6][7].…”
Section: Introductionmentioning
confidence: 99%